How note-taking and note-using affects the benefit of interleaving over blocking. - Little, Jeri L.; Fealy, Josephine C. M.; Kobayashi, Koki; Roth, Sarah (Memory & Cognition, 2026)
Interleaving items from different categories is often better for learning than blocking items by category, but research on the interleaving effect has neglected situations in which people can take notes. In addition to the practical reasons for examining note-taking, notes also provide insight into participants' thought processes during learning. In two experiments, participants studied paintings by different artists, with paintings by half of those artists blocked by artist and paintings by the other half interleaved with paintings by other artists. We manipulated whether participants took notes. Then, participants classified new paintings by the studied artists (in Experiment 1, all note-takers used their notes on the test; in Experiment 2, half of the note-takers used their notes on the test and half did not). Across both experiments, we found an interaction between sequence and note-taking conditions. In the no-notes condition, interleaving was more effective than blocking for classifying new paintings. However, this benefit was significantly reduced when participants took notes but could not use them on the test and eliminated when they could take notes and use them on the test. Additionally, participants' notes tended to contain object and style characteristics, and the presence of critical style characteristics in participants' notes predicted their performance. This research sheds light on thought processes in category learning and may have implications for educational contexts.